Kistermelői húsfeldolgozás Pest megyében - Marosi, Tibor; Takácsné Fajt, Éva (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
This paper presents the analysis of the activities of small producers, particularly in thc mcat processing area. The focuses of the development are the trade and economic environment of small producers. The base of analysis is the quarterly reports of Pest County Government Office Food Chain Safety and Animál Health Directorate. These include the number and distribution of small producers in Pest County. Furthermore the compliance with legal requirements and the rcsults of official controis are reviewed.